Do low-skilled migrant remittances help achieve SDG 10? - KRATOU, Hajer (2023)
In this paper we explore the role migrant skill composition plays in remittances and income inequality’ relationships, using a panel study of 53 African countries over the period 1990–2020 and refer ring to two strands of literature that demonstrate that (1) highly skilled migrants widen the income gap in the home country; and (2) they have fewer incentives to remit compared to their less-skilled compatriots. The instrumental variable technique was employed to estimate a dynamic panel data model whilst rectifying endogeneity issues. The findings reveal that a policy that shifts the migrant skill composition toward the less-skilled workers could channel more remittance funds to poor households, resulting in diminishing the income disparity in the home country. Migration policies attempt ing to mitigate the brain drain and facilitate the migration of low- skilled workers would enable the attenuation of the income inequality gap.